The Law of Propagation in Hadith Perspective - Hilman Mauludin; Ifah Khadijah (UIN Sunan Gunung Djati Bandung, 2019)
This article tries to discuss about law of propagation in hadith perspective. By Using library research, this article found that for every Muslim, da'wah is an obligation that cannot be negotiable. The obligation of da'wah is something that is impossible to avoid from his life, because it is very attached to self-recognition as adherents of Islam. Indirectly, every Muslim as the bearer of missionary mission. Based on the results of the analysis, especially the study of the hadith and according to most scholars in general the da'wah law is farḍ kifāyah, meaning that if it has been done by a group of people, the burden of that obligation falls from the others.